Teoría y praxis de la penitencia en la Segovia bajomedieval - Esteban Herrera (Estudios de Historia de España, 2016)
The following study deals with the subject of the sacrament of penance in the Segovian Diocese during the Lower Middle Ages. It considers its doctrinal aspects, the instructions followed by the priests to correctly administer it and its correct practice in the different parishes that made up the diocese. If the Higher ecclesiastical hierarchies placed a lot of emphasis and effort into promoting the obligatory annual confession, following the instructions of the IV Lateran Council, the every-day parish life spoke only of a partlyachieved goal that was only completely successful after the Reformation. Said failing did not come from scarce or weak popular devotion but from the lack of an effective control of the lower clergy.